Conservação da qualidade de maçãs mutantes de ‘gala’ tratadas com fitorreguladores e armazenadas em atmosfera controlada dinâmica - Anese, Rogerio de Oliveira (2017)
Being the harvest time of apples concentrated in a short period, fruit storage is needed for market regulation. New storage technologies are being developed, such as dynamic controlled atmosphere with respiratory quotient (DCA-RQ), that needs to be evaluated under different temperatures and with the application of growth regulators such as aminoethoxyvinylglycine (AVG), naphthalene acetic acid (NAA) and 1-methylcyclopropene (1-MCP). This thesis is composed of four papers, which resulted from studies with the following objectives: to evaluate volatile compounds concentration in ‘Galaxy’ and ‘Royal Gala’ apples stored under DCA-RQ, DCA with chlorophyll fluorescence (DCA-CF), controlled atmosphere (CA) with and without 0,625 μL L-1 of 1-MCP application; to evaluate if DCA-RQ and DCA-CF allow employing higher temperatures during apple storage; to evaluate the effect of the application of AVG (0.83 kg ha-1) in combination with NAA (40g ha-1), as well as the effects of 1-MCP in the production of volatile compounds and physical-chemical quality of apples stored under DCA monitored with chlorophyll fluorescence and respiratory quotient; identify if the stress by low O2 partial pressure during RQ measurement has an effect on apple quality conservation. ‘Galaxy’ and ‘Royal Gala’ apples were stored for 9 months plus 7 days at 20 °C. It is worth noting that ‘Galaxy’ apples stored under DCA-RQ1.5 maintained better quality when compared to CA, ultralow oxygen (ULO – 0.4kPa) and DCA-CF, also increasing the production of esters responsible for the aroma. Besides, 1-MCP reduced volatile compounds concentration, even in apples stored under DCA-RQ1.5. Likewise, DCA-CF had a similar effect to ULO with 0.4 kPa of O2. The DCA-RQ1.3 and DCA-CF allowed storing ‘Galaxy’ apples under temperatures higher (2.0 and 2.5 °C) than recommended (1.5 °C). In addition, 1-MCP application did not have additional effects when fruit were stored under DCA and higher temperatures. Higher temperatures (2.0 and 2.5 °C) could be used without reducing the production of important volatile compounds. In DCA-RQ, the stress by low O2 employed during RQ measurement has presented a beneficial effects, with fruit maintaining higher flesh firmness, lower mealiness and decay incidence compared to fruit without RQ calculation. ‘Royal Gala’ apples stored under DCA-RQ1.3 and DCA-CF, submitted to the application of AVG and NAA during prehavest did show an increase in the concentration of volatile compounds. However, the combination of AVG plus NAA and the storage under DCA-RQ1.3 or DCA-CF presents an excellent alternative for storing apples, because maintains higher flesh firmness, reduce physiological disorders and maintain higher percentage of healthy fruit.